Physical training of highly qualified paracanoists in a year macrocycle - Yu.B. Kazaryan; G.M. Yulamanova; A.Yu. Kostarev; A.V. Danilov (Theory and Practice of Physical Culture, 2023)
Objective of the study was to scientifically substantiate the content of the physical training of highly qualified paracanoists in a one-year macrocycle and evaluate the effectiveness of its use in the training process. Methods and structure of the study. The experiment involved 9 highly skilled paracano athletes classified as LTA-IVF according to the ICF classification. The content of the physical training of athletes of this category is structured with the allocation of three stages that differ from each other in tasks, organization, goals, content of methodological techniques and a set of actions, means that determine the mechanisms for their use to achieve the highest possible sports results of highly qualified paracanoists. Results and conclusions. It was determined that the content of physical training with the allocation of three successively implemented stages of highly qualified paracanoists in the annual macrocycle contributed to the increase in the level of physical fitness of athletes in this category, as well as to improve their competitive results.